Prophage Rs551 and Its Repressor Gene orf14 Reduce Virulence and Increase Competitive Fitness of Its Ralstonia solanacearum Carrier Strain UW551 - Ahmad, Abdelmonim Ali; Stulberg, Michael J.; Huang, Qi (Frontiers in Microbiology, 2017)
We previously characterized a filamentous lysogenic bacteriophage, ϕRs551, isolated directly from the race 3 biovar 2 phylotype IIB sequevar 1 strain UW551 of R. solanacearum grown under normal culture conditions. The genome of ϕRs551 was identified with 100% identity in the deposited genomes of 11 race 3 biovar 2 phylotype IIB sequevar 1 strains of R. solanacearum, indicating evolutionary and biological importance, and ORF14 of ϕRs551 was annotated as a putative type-2 repressor. In this study, we determined the effect of the prophage and its ORF14 on the virulence and competitive fitness of its carrier strain UW551 by deleting the orf14 gene only (the UW551 orf14 mutant), and nine of the prophage’s 14 genes including orf14 and six out of seven structural genes (the UW551 prophage mutant), respectively, from the genome of UW551. The two mutants were increased in extracellular polysaccharide production, twitching motility, expression of targeted virulence and virulence regulatory genes (pilT, egl, pehC, hrPB, and phcA), and virulence, suggesting that the virulence of UW551 was negatively regulated by ϕRs551, at least partially through ORF14. Interestingly, we found that the wt ϕRs551-carrying strain UW551 of R. solanacearum significantly outcompeted the wt strain RUN302 which lacks the prophage in tomato plants co-inoculated with the two strains. When each of the two mutant strains was co-inoculated with RUN302, however, the mutants were significantly out-competed by RUN302 for the same colonization site. Our results suggest that ecologically, ϕRs551 may play an important role by regulating the virulence of and offering a competitive fitness advantage to its carrier bacterial strain for persistence of the bacterium in the environment, which in turn prolongs the symbiotic relationship between the phage ϕRs551 and the R. solanacearum strain UW551. Our study is the first towards a better understanding of the co-existence between a lysogenic phage and its carrier plant pathogenic bacterial strain by determining the effect of the prophage ϕRs551 and its repressor on the virulence and competitive fitness of its carrier strain UW551 of R. solanacearum.